A study on criteria for selecting outsource company in MASkargo Sdn. Bhd. / Mohd Faiz Abd Rauf - Abd Rauf, Mohd Faiz (Faculty of Business and Management, 2009)
Outsourcing is subcontracting a process, such as product design or manufacturing, to a third-party company. The decision to outsource is often made in the interest of lowering cost or making better use of time and energy costs, redirecting or conserving energy directed at the competencies of a particular business, or to make more efficient use of land, labor, capital, (information) technology and resources. Some of them also outsourcing because they did not have the knowledge in that this study is about to find out what is the criteria that important for a company to consider before hiring an outsource company. The objective of this research is to come out with a solution about how to choose the right outsource company.